Upregulation of Neural Cell Adhesion Molecule 1 and Excessive Migration of Purkinje Cells in Cerebellar Cortex - Shabanipour, Shahin; Jiao, Xiaodan; Rahimi-Balaei, Maryam; Aghanoori, Mohamad Reza; Chung, Seung H.; Ghavami, Saeid; Consalez, G. Giacomo; Marzban, Hassan (Frontiers in Neuroscience, 2022)
Purkinje cells (PCs) are large GABAergic projection neurons of the cerebellar cortex, endowed with elaborate dendrites that receive a multitude of excitatory inputs. Being the only efferent neuron of the cerebellar cortex, PCs project to cerebellar nuclei and control behaviors ranging from movement to cognition and social interaction. NCAM1 is widely expressed in the embryonic and postnatal development of the brain and plays essential roles in neuronal migration, axon pathfinding and synapse assembly. However, despite its high expression levels in cerebellum, little is known to date regarding the role(s) of NCAM1 in PCs development. Among other aspects, elucidating how the expression of NCAM1 in PCs could impact their postnatal migration would be a significant achievement. We analyzed the Acp2 mutant mouse (nax: naked and ataxia), which displays excessive PC migration into the molecular layer, and investigated how the excessive migration of PCs along Bergmann glia could correlate to NCAM1 expression pattern in early postnatal days. Our Western blot and RT-qPCR analysis of the whole cerebellum show that the protein and mRNA of NCAM1 in wild type are not different during PC dispersal from the cluster stage to monolayer formation. However, RT-qPCR analysis from FACS-based isolated PCs shows that Ncam1 is significantly upregulated when PCs fail to align and instead overmigrate into the molecular layer. Our results suggest two alternative interpretations: (1) NCAM1 promotes excessive PC migration along Bergmann glia, or (2) NCAM1 upregulation is an attempt to prevent PCs from invading the molecular layer. If the latter scenario proves true, NCAM1 may play a key role in PC monolayer formation.